Life cycle, feeding behavior and nature of damage of sweet potato leaf moth, Agrius cingulata (Fabricius) and Agrius Convolvuli (Linnaeus) (Lepidoptera: Sphingidae) - Halder, Bani; Sultana, Shanjida; Akter, Tangin; Begum, Shefali (Dhaka University Journal of Biological Sciences, 2018)
The sweet potato hornworm Agrius cingulata and Agrius convolvuli are destructive pests of sweet potato. This study was conducted to observe the life cycle and the feeding potential of larval instars of A. cingulata and A. convolvuli under laboratory condition (28 ± 4ºC, 70 ± 4% RH and 12 L : 12 D photoperiod). The laboratory study revealed an average incubation period of 6 ± 0.50 days for A. cingulata and 4 ± 0.50 days for A. convolvuli, larval duration of 42 ± 1 days for A. cingulata and 24 ± 1 days for A. convolvuli, pupation period 26±1 days for A. cingulata and 14±1 days for A. convolvuli. The life span from egg to adult stage, on an average, was 73 days for A. cingulata and 55 days for A. convolvuli. The larval feeding potential was determined by both the maturity and availability of suitable leaves although mature larvae were observed to feed on the stems and flower of the host plant in absence of suitable leaves. The larvae of both hornworms preferred mostly the young and mature leaves. The caterpillars of A. cingulata and A. convolvuli were found voracious feeder. The nature of damage of sweet potato hornworm mostly occurred on the host-plant. The yield of sweet potato was reduced due to the infestation of the pests. Dhaka Univ. J. Biol. Sci. 27(2): 125-134, 2018 (July)